Beyond socioemotional wealth: taking another step toward a theory of the family firm. (21st November 2016) - Chrisman, James J.; Holt, Daniel T.
Abstract : Purpose: The purpose of this paper is to explain how the concept of socioemotional wealth can be combined with other important concepts in the family firm literature to develop a theory of the family firm. Design/methodology/approach: This is a conceptual paper based on a review of the paper of Martin and Gómez-Mejía in this issue as well as the family business literature in general. Findings: Martin and Gómez-Mejía (this issue) present a theoretical model and propositions on the relationship between socioemotional and financial wealth that advances understanding of family firm decision-making. That paper provides an initial step toward a theory of the family firm that can explain why firms select the family form of organization to conduct economic activities, what determines their scale and scope and why heterogeneity is observed among family firms. This commentary takes another step toward such a theory by discussing how the combined consideration of goals, governance and resources could be used to address the above three questions. Originality/value: The precepts of a new theory of the family firm is presented that incorporates the concepts of goals (socioemotional wealth), governance (family ownership and control) and resources (familiness) of family firms to explain why family firms exist and potentially thrive as well as to explain the heterogeneity among family firms.